MEMAHAMI MAKNA DEMOKRASI DALAM PENDIDIKAN DEMOKRASI - Hutabarat, Dany Try Hutama; Sinta, Nuria; Dwiva, Nur Aulia; Raihandi, Muhammad Abiyyu; Ardiansyah, Ari; Febrian, Sazri; Akbar, Ghani (Transpublika Publisher, 2021)
The purpose of this study is to identify and comprehend the meaning of democracy through democratic education. This research method is qualitative approach based on a literature review. Democracy is a way of life that must develop and flourish in citizens, both those in positions of authority (state administration) and those who are not in positions of authority (ordinary citizens). This democratic way of life will result in a democratic culture. To support the form of government and political system, a positive attitude toward life and a democratic culture are required. Democracy education essentially establishes a democratic culture that will eventually become the democratic structure.